Molecular Viscosity Sensors with Two Rotators for Optimizing the Fluorescence Intensity-Contrast Trade-off - Lee, Seung Chul; Lee, Chang Lyoul; Heo, Jeongyun; Jeong, Chan Uk; Lee, Gyeong Hui; Kim, Sehoon; Yoon, Woojin; Yun, Hoseop; Park, Sung O.; Kwak, Sang Kyu; Park, Sung Ha; Kwon, O. Pil (Chemistry - A European Journal, 2018)
Invited for the cover of this issue is the collaborative team of the groups of O-Pil Kwon at Ajou University, Chang-Lyoul Lee at Advanced Photonics Research Institute (APRI), Gwangju Institute of Science and Technology (GIST), Sehoon Kim at Korea Institute of Science and Technology (KIST), Hoseop Yun at Ajou University, and Sang Kyu Kwak at Ulsan National Institute of Science and Technology (UNIST). The image depicts fluorescent molecular rotors by introducing two rotational groups with high fluorescence contrast and cellular fluorescence imaging for mapping cellular viscosity. Read the full text of the article at 10.1002/chem.201704036.
Keywords: Cellular fluorescence imaging; Collaborative teams; Fluorescence intensities; Molecular rotors; Molecular viscosity; Photonics research institutes; Science and Technology; Trade off